2013
DOI: 10.1021/jp406625e
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Contact Recombination and Open-Circuit Voltage in Polymer Solar Cells via Self-Assembled Monolayer Adsorption at the Organic–Metal Oxide Interface

Abstract: We adsorbed fluorinated-alkyl and hydrogenated-alkyl phosphonic acid derivatives onto indium tin oxide (ITO) to form self-assembled monolayers (SAMs). Polymer solar cells having these treated ITOs as anodes display open-circuit voltages (V ocs) that are higher than those with bare ITO as anodes. Although the work function of ITO can be significantly tuned by SAM adsorption, the position of the Fermi level of the anode with respect to the hole transport level in the polymer active layer is essentially the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 71 publications
2
45
0
Order By: Relevance
“…The presence of these new interfacial states upon surface modification can impact charge injection or extraction when interfaced with active organic layers, which is critical to improving device performance in organic optoelectronic applications. Similar impact has been observed in recent experimental applications using phosphonic acids as surface modifiers on ITO electrodes …”
Section: Discussionsupporting
confidence: 84%
“…The presence of these new interfacial states upon surface modification can impact charge injection or extraction when interfaced with active organic layers, which is critical to improving device performance in organic optoelectronic applications. Similar impact has been observed in recent experimental applications using phosphonic acids as surface modifiers on ITO electrodes …”
Section: Discussionsupporting
confidence: 84%
“…23 But, on the other hand, this strategy also increases the recombination loss due to the increase of the interfacial area between NWs and CQDs, thus decreasing the device performances, especially the open circuit voltage (V oc ). 25,[27][28][29][30][31] For example, TiO 2 layers were introduced by Cao and co-workers to modify the surface of mesoporous ZnO electrodes, which improved the photovoltaic performances of CdS/CdSe QDSSCs. Studies on the metal oxide component have been rarely reported and mostly focused on their morphological properties and doping effect.…”
Section: Introductionmentioning
confidence: 99%
“…An attractive solution is to combine small molecule modifiers for work function control and defect passivation with the selective oxide contacts . However, previous work has been carried out using deposition methods, which expose the oxide to excess solvent—dip coating or substrate soaking for one to many days in a dilute solution.…”
Section: Introductionmentioning
confidence: 99%